냉간모드에서의 이륜자동차 VOCs 배출특성연구 - 이종태; Jong Tae Lee; 유흥민; Heung Min Yoo; 손지환; Ji Hwan Son; 윤창완; Chang Wan Yun; 문선희; Sun Hee Mun; 박규태; Gyu Tae Park; et al. (한국분무공학회지, 2015)
Recently, some researchers have been carried out risk assessment of vehicles exhaust on human health. Especially, some of VOCs which is non-controlled, was classified to hazardous pollutant, such as 1,3-Butadiene and BTEX(Benzene, Toluene, Ethylbenzene and Xylene). Therefore, the profile on non-controlled pollutant may be needed in the future, because it would be critical data or information to control them. Additionally, with increasing amount of motorcycle, the source profiling is essential for estimating emission factor and amount on motorcycle exhaust. For these, in this study, imported motorcycles (8 vehicles) were selected as a test model while considering the increasing ratio on sales volume between 2013 and 2014; it was also compared with domestic motorcycles on those. The experiment was conducted by driving mode, UDC and ECE+EUDC that made from EURO III. In addition, it was performed at cold start driving mode without effect by displace- ment, for evaluating only correlation of BTEX with HC. In order to apply the ratio (m,p-Xylene/o-Xylene) as a marker, the ratio was compared with those of tunnel, road side and residential area. As a result, it showed best correlation (R2=0.98) among those. In the future, it has to be considered as a marker for effect evaluation to atmospheric environment by exhaust emission.